Analisis Daya Dukung Lingkungan Berdasarkan Evaluasi Kemampuan Lahan sebagai Landasan Pengelolaan Perkebunan Kelapa Sawit Rakyat - Nuriman, Muhammad; Adelina, Winna; Alkadrie, Rachmad Hafiz Zulfifar (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2024)
The utilization of land that is not aligned with its environmental carrying capacity is a significant issue in Indonesia. One affected sector is oil palm plantations, which covered an area of 16.38 million hectares in 2019. However, the government policy through Presidential Instruction Number 8 of 2018 halted this expansion. This policy also applies to independent farmers who must adhere to the principles and criteria of the RSPO (Roundtable on Sustainable Palm Oil), including practices to maintain soil fertility, control erosion and soil degradation, and plan development locations based on soil surveys. This study aims to evaluate the land capability of independent oil palm plantations in Sintang Regency. The methods used include soil surveys and land evaluation with the collection of soil morphology data and soil type classification. The study results show significant differences between the soil type map data issued by BBSDLP in 2010 and field verification results. Land evaluation identified four different soil units, each requiring specific management based on limiting factors such as plant root penetration, water excess, soil texture, slope gradient, and waterlogging. Proper land management includes soil and water conservation techniques, cover cropping, liming, and good drainage. Water management on peatlands must also consider environmental aspects to prevent ecosystem damage. With proper evaluation and management, land productivity can be sustainably increased.